Pengembangan Koleksi Perpustakaan sebagai Strategi Meningkatkan Minat Baca Siswa - Beny Sintasari; Dita Dzata Mirrota; Binti Masrufa; Nur Munir; Shafitri Ayu Ramadani (At Tadbir: Islamic Education Management Journal, 2025)
This study aims to analyze the strategy of library collection development and efforts to increase students' reading interest at SMPN 1 Mojowarno Jombang. The focus of the study includes the evaluation of library collection needs, collection procurement and selection mechanisms, and the influence of the environment and habits on students' reading interest. The method used is a qualitative descriptive approach with data collection techniques through in-depth interviews, observations, and documentation studies. The results of the study indicate that collection evaluation is carried out routinely by utilizing borrowing and visit data to determine the books that are most in demand by students, such as supporting books and novels. Collection procurement is based on the curriculum and academic needs, involves active participation from teachers, and utilizes BOS funds to enrich the literacy collection. One of the strategies implemented is the rotation of collections between classes, which allows students to access various types of reading. Although students' reading interest is still relatively low, efforts to get used to reading before learning begins, the provision of comfortable library facilities, and promotion of collections by teachers have succeeded in significantly increasing students' reading interest. This study contributes to the development of school library collection management and efforts to increase student literacy, and offers recommendations for further research to explore other factors that influence students' reading interest in secondary schools.